Income Thresholds and Income Classes - Conchita D'Ambrosio; Pietro Muliere; Piercesare Secchi (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
This paper proposes a method for detecting income classes based on the change-point problem. There is an increasing demand for such a method in the literature. Computation of polarization indices requires a pre-grouping of the incomes. Similarly, indices of social exclusion and sometimes indices of income inequality require detection of thresholds. The estimation procedure is implemented using a bootstrap technique. Finally, an application of the method to EU member states and to the United States is also considered.
Keywords: D31; 330; income distribution; change-point; thresholds; Einkommensverteilung; Disparitätsmass; Soziale Isolation; Theorie; EU-Staaten; Vereinigte Staaten; change-point